KONTEKS KOMUNIKASI NETIZEN DI MEDIA SOSIAL: Studi Netnografi Komunikasi terhadap Perilaku Bermedia Netizen di Akun Instagram Jokowi - Elvianti, Elvianti; Wibowo, Ari (KOMUNIKASIA: Journal of Islamic Communication and Broadcasting, 2021)
This article aims to explain the context of communication and media behavior of netizens on Jokowi's Instagram account. There are two fundamental problems behind this research, namely; 1) the high participation of netizens in responding to status and posts on Jokowi's account; 2) the emergence of variations in netizen comments in the form of support and hate speech. Therefore, to analyze in depth these problems, this research is supported by a qualitative approach with the ethnographic method of communication. This method is used to find the reasons (motives) and context of communication events that arise from the two virtual communities. The data or information needed in this study is based on the context of the speech community behavior that occurs in the comments column on Jokowi's Instagram account. Netizens who actively argued and gave statements in the comments column were analyzed with and concepts, namely the concept of maxim of wisdom and maxim of appreciation. There are groups or communities that like to give negative comments and there are also communities that give positive responses.